Da "causa constitucional" à "causa da independência" : os discursos e debates parlamentares da representação da Bahia nas Cortes Gerais de Lisboa e na Assembleia Geral Constituinte do Rio de janeiro (1821-1823) - Lemos, Antonio Cleber da Conceição (2018)
This dissertation has as general objective to analyze the speeches and debates of the Bahian deputies in the General Courts of Lisbon (1821-1822) and the General Constituent Assembly of Rio de Janeiro (1823), in order to understand the process of political participation of the political leaders of the constitutional experiences. Its specific objectives are: to analyze the debates of the Bahia deputation; to discuss the construction of the speeches of the Bahian deputies about the relevance of the province for the construction of the State; understand the proposals of formation of the political pact by the Bahian deputies. The justification for this study lies in the relevance of the situation of armed conflict in Bahia to the events that unfolded in the process of Brazilian Independence, and the formation of the constitution was a fundamental condition for the foundation of the State, where war in Bahia was also relevant fact to the same process. Among the analyzed sources, are the diaries of the Courts and Assembly, periodicals, correspondence, minutes and reports. The methodology used was inspired by Renewed Political History and Social History of Concepts, which seek to discuss political processes based on concepts, discourses, institutional redefinitions and projects put in dispute by the subjects that act in the public spheres of power, constituting political cultures. However, the work does not lose sight of the analysis of events, institutions and trajectories of political subjects, so that it is possible that the discourses investigated are understood.